Fungal Endophytes Exert Positive Effects on Colobanthus quitensis Under Water Stress but Neutral Under a Projected Climate Change Scenario in Antarctica - Hereme, Rasme; Morales Navarro, Samuel; Ballesteros, Gabriel; Barrera, Andrea; Ramos, Patricio; Gundel, Pedro Emilio; Molina Montenegro, Marco A. (Frontiers in Microbiology)
Functional symbiosis is considered one of the successful mechanisms by which plants that inhabit extreme environment improve their ability to tolerate different types of stress. One of the most conspicuous type of symbiosis is the endophyticism. This interaction has been noted to play a role in the adaptation of the native vascular plant Colobanthus quitensis to the stressful environments of Antarctica, characterized by low temperatures and extreme aridity. Projections of climate change for this ecosystem indicate that abiotic conditions will be less limiting due to an increase in temperature and water availability in the soil. Due to this decrease in stress induced by the climate change, it has been suggested that the positive role of fungal endophytes on performance of C. quitensis plants would decrease. In this study, we evaluated the role of endophytic fungi on osmoprotective molecules (sugar production, proline, oxidative stress) and gene expression (CqNCED1, CqABCG25, and CqRD22) as well as physiological traits (stomatal opening, net photosynthesis, and stomatal conductance) in individuals of C. quitensis. Individual plants of C. quitensis with (E+) and without (E−) endophytic fungi were exposed to simulated conditions of increased water availability (W+), having the current limiting water condition (W−) in Antarctica as control. The results reveal an endophyte-mediated lower oxidative stress, higher production of sugars and proline in plants. In addition, E+ plants showed differential expressions in genes related with drought stress response, which was more evident in W− than in W+. These parameters corresponded with increased physiological mechanisms such as higher net photosynthesis, stomatal opening and conductance under presence of endophytes (E+) as well as the projected water condition (W+) for Antarctica. These results suggest that the presence of fungal endophytes plays a positive role in favoring tolerance to drought in C. quitensis. However, this positive role would be diminished if the stress ...